Reduced cortical thickness and its association with social reactivity in children with autism spectrum disorder - Kalmar, Julia; Henze, Romy; Parzer, Peter; Haffner, Johann; Brandeis, Daniel; Poustka, Luise (Psychiatry research, 2015)
Symptomatology and behavioral characteristics in autism spectrum disorders (ASD) have increasingly been linked to abnormalities in early brain growth patterns of affected children. Studies investigating specific components of gray matter structure, such as cortical thickness (CT), have produced conflicting results, and have rarely included additional measures of social impairment. In the present study, we applied a surface-based whole brain analysis to investigate CT in a sample of 36 pre-adolescent children [18 subjects with ASD (IQ mean: 111) and 18 healthy controls (IQ mean: 112.8), age range 6-12 years]. The CT analysis revealed widespread, but mostly left-hemispheric thinning in frontal, temporal, parietal and occipital brain areas related to the theory-of-mind network and the heteromodal association cortex. In an exploratory analysis, CT was observed to be differently associated with social impairment in children with ASD compared with typically developing children. The affected neuroanatomical regions are related to characteristic deficits in language, cognition and behavior that are often observed in the disorder. The relationship between social impairment and CT in children with ASD and controls seems to indicate aberrant developmental trajectories in ASD emerging early in life.
Gesehen am 21.03.2018